Factors that Hinder Effective Management and the Supply of Clean Potable Water at eThekwini Municipality in KwaZulu-Natal - Gumbi, N.; Rangongo, M. F. (International Conference on Public Administration and Development Alternatives, 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa, 2018)
The paper intends to identify challenges for eThekwini District Municipality to supply sustainable fresh drinkable water, explore success factors in terms of efficient water supply and investigate feasible suggestions for future effective management and supply of adequate water to all the citizens of the municipality.Water is a necessity for life, as well as for development. No nation can afford to ignore the issue of effective water management and supply for its community. Water management is especially challenging for water scarce countries like South Africa. This paper presents a study that examines the factors that hinders effective management and supply of clean potable water in eThekwini Municipality. A desktop analysis was conducted on the existing research studies, as well as reports in evaluating the trials as well as success factors that eThekwini Municipality had encountered in managing and supplying water to their community. The findings reflect that the task of managing and supplying water emanates from many factors such as: infrastructure degradation; climate change; financial sustainability; ineffectiveness and inefficiency on inward-looking local government still prevalent in the Municipality more especially in the rural areas. This study recommends the importance of the implementation of effective water supply management strategy that will work for the province.Six strategic priority areas have been identified in order to achieve and address the encounters faced by the Municipality. These strategic priorities provide the basis for the identification of programmes and projects within the Integrated Development Plan (IDP) that will help refine and evaluate a strategic approach to ensure that these strategies are being implemented for the benefit of their community.
Journal article published in The 3rd Annual International Conference on Public Administration and Development Alternatives, 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: Economic development; Service delivery; Water management; Water supply; Water supply